2018
DOI: 10.1002/jcb.26853
|View full text |Cite
|
Sign up to set email alerts
|

S6K1 controls epigenetic plasticity for the expression of pancreatic α/β cell marker genes

Abstract: The failure of insulin production by pancreatic β cells is a common hallmark of type 1 diabetes mellitus (T1DM). Because administration of exogenous insulin is associated with diabetes-derived complications, endogenous α to β cell transition can be an attractive alternative. Although decreased β cell size and hypoinsulinaemia have been observed in S6K1-deficient mice, the molecular mechanism underlying the involvement of S6K1 in the transcriptional regulation of insulin remains elusive. Here, we show that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 55 publications
(130 reference statements)
0
2
0
Order By: Relevance
“…While insulin-secreting β-cells and glucagon-secreting α-cells have different physiological functions, a study revealed that human α, β, and exocrine cells share similar profiles of histone methylation of H3K4me3 and H3K27me3, suggesting an epigenomic plasticity of islet cells and their reprogrammable potentials to treat diabetes (Bramswig et al, 2013). For example, the activation of the S6K1 kinase promotes α to β-cell transition by activating β-cell genes while repressing α-cell genes through histone methylation of the activating H3K4me3 and repressing H3K27me3, respectively (Yi et al, 2018). Human pancreatic α-cells can also be reprogrammed into insulin-producing cells by PDX1, and when transplanted, can treat diabetic mice (Furuyama et al, 2019).…”
Section: Histone Methylation/demethylationmentioning
confidence: 99%
“…While insulin-secreting β-cells and glucagon-secreting α-cells have different physiological functions, a study revealed that human α, β, and exocrine cells share similar profiles of histone methylation of H3K4me3 and H3K27me3, suggesting an epigenomic plasticity of islet cells and their reprogrammable potentials to treat diabetes (Bramswig et al, 2013). For example, the activation of the S6K1 kinase promotes α to β-cell transition by activating β-cell genes while repressing α-cell genes through histone methylation of the activating H3K4me3 and repressing H3K27me3, respectively (Yi et al, 2018). Human pancreatic α-cells can also be reprogrammed into insulin-producing cells by PDX1, and when transplanted, can treat diabetic mice (Furuyama et al, 2019).…”
Section: Histone Methylation/demethylationmentioning
confidence: 99%
“…In contrast, adipose tissue of mice depleted with S6k1 shows lower levels of pS36 H2B and H3K27me3 [ 181 ], highlighting strategies to employ specific S6K1 inhibitors to suppress obesity and overcome insulin resistance, bypassing mTORC2 inhibition. In islet cells, S6K1 is capable of promoting H3K4me3 and inhibiting H3K27me3 to support transcription marker genes of β cells and suppress those of α cells [ 182 ]. It is believed that the pancreatic cell transition induced by S6K1 might provide basic clues for type I diabetes.…”
Section: Downstream Substrates and Biological Roles Of S6kmentioning
confidence: 99%